Chapter 31 Re-imagining the Northeast in India, again Did geography sidestep history in Vision (2020)? - D'Souza, Rohan (Taylor & Francis, 2018)
"Northeast India is a multifaceted and dynamic region that is constantly in focus because of its fragile political landscape characterized by endemic violence and conflicts. One of the first of its kind, this reader on Northeast India examines myriad aspects of the region - its people and its linguistic and cultural diversity. •The chapters here highlight the key issues confronted by the Northeast in recent times: its history, politics, economy, gender equations, migration, ethnicity, literature and traditional performative practices. •The book presents interlinkages between a range of socio-cultural issues and armed political violence while covering topics such as federalism, nationality, population, migration and social change. •It discusses debates on development with a view to comprehensive policies and state intervention. With its a nuanced and wide-ranging overview, this volume makes new contributions to understanding a region that is critical to the future of South Asian geopolitics. The book will be of great interest to scholars and researchers of contemporary Northeast India as well as history, political science, area studies, international relations, sociology and social anthropology. It will also appeal to those interested in public administration, regional literature, cultural studies, population studies, development studies and economics."